Photodegradation of macroplastics to microplastics : A laboratory study on common litter found in urban areas - Svedin, Jonathan (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2020)
During the last 60 years the plastic production has increased more than 190 times and plasticpollution both at sea and land is a growing issue. Every year millions of tons of plastic waste fromland reaches the oceans, but the land-based sources are diffuse. One possible source of plasticwaste and microplastics are from plastic litter in urban areas which is common all over the world.The aim with this laboratory study was to study the photodegradation patterns of macroplasticsthat is usually found as litter in urban areas to contribute with knowledge and to theunderstanding of how macroplastics degrade to microplastics. The laboratory study wasstructured around the use of ultraviolet light exposure from UVA 340 nm lamps to acceleratephotodegradations of plastics in air. The test was divided into four different time intervals: stage7 days, stage 14 days, stage 28 days, and stage 56 days to study the evolution of plasticfragmentation over time. Effect of the UV radiation and test duration were combined to derivethe equivalent real time duration. Using Luleå as a benchmark the computed equivalence were0.27 years for every seven days of UV exposure. For stage 7d, a test with different mediums(water and air) were performed to compare the degradation processes between differentenvironments. However, for the longer time intervals air was the only tested environment. Newplastic products were bought which were among the most produced types of plastic or mostcommon plastic litter. The plastics were the following: polystyrene (PS) as plastic coffee cup lid,polypropylene (PP) as chocolate wrapping, polyethylene terephthalate (PET) as plastic bottle,low- density polyethylene (PE-LD) as plastic grocery bag and cellulose acetate (CA) as cigarettefilter or butts. The analytical techniques used were a particle size and number counter, with theselected particle size interval between 4-120 μm, and a camera mounted microscope to studyshapes of microplastic particles. Before photographing the particles, the samples were filtered ona ...